Endoscopic surveillance or ablation for Barrett’s esophagus? - Inadomi, John M.; Saxena, Nina (Translational Gastroenterology and Hepatology, 2018)
The incidence of esophageal adenocarcinoma (EAC) is rising and the only known precursor of this disease is Barrett’s esophagus (BE). EAC mortality remains high, prompting strategies to screen individuals with gastroesophageal reflux disease (GERD) symptoms to identify BE and conduct surveillance in order to detect neoplasia at a stage that is amenable to cure. The effectiveness of endoscopic eradication therapy has been improving with reduced harms, yet it is unclear which patients will benefit from this procedure. This chapter reviews the evidence supporting surveillance for BE to reduce mortality from EAC and combines these results with economic analyses to identify the optimal means to manage patients with BE with high-grade dysplasia, low-grade dysplasia, or no dysplasia.